Compressive strength and fire resistance of mortar containing crushed cockle shell as fine aggregate replacement - Hanis Nadiah, Ruslan; Khairunisa, Muthusamy; Mohd Faizal, Md Jaafar; Nabilla, Mohamad; Nur Farah Aziera, Jamaludin (Elsevier Ltd, 2024)
Continuous extraction of sand from the river without any control would disrupt the ecosystem in the river. In addition, disposal of cockle shells as garbage contributes to pollution and an unpleasant atmosphere. Thus, the current study investigates the influence of substitution of crushed cockle shell as a partial fine aggregate on the compressive strength and fire resistance of mortar. Five mortar mixes were created by using 0%, 10%, 20%, 30%, and 40% crushed cockle shell replacement by weight of sand. Compressive strength and fire resistance tests were carried out. The results demonstrate that using 10% crushed cockle shell produces mortar with the highest compressive strength value. All mixes met the target strength at 28 days, with values ranging from 17.52 MPa to 22.21 MPa. Up to 600 °C, the mortar containing 10% crushed cockle shell exhibits more mass and strength loss almost compared to control mortar. Excessive use of crushed cockle shell results in greatest mass loss and strength when exposed to high temperatures. On overall, the incorporation of cockle shell substitute as fine aggregate would reduce the demand for natural river sand and pollution caused by cockle shell disposal.